"Celebrity 2.0 and beyond!" Effects of Facebook profile sources on social networking advertising. (February 2018) - Jin, Seunga Venus
Abstract: Two experiments examined the effects of different sources (celebrity versus peer consumer) of celebrity-brand-related user-generated content (UGC) embedded in a social networking site (SNS). Consistent with the basic premises of warranting theory (stronger effects of other -endorsement than self -endorsement) and social identity theory (more positive effects of ingroup than outgroup ), Experiment 1 demonstrated more positive effects of celebrity brand endorsements posted on a peer consumer's ( other ; in-group identity ) Facebook profile page on source credibility perception and parasocial interaction with the celebrity than celebrity brand endorsements posted on the celebrity 's own ( self; out-group identity ) Facebook profile page. Social identification mediated the effects of the Facebook profile source on parasocial interaction with the celebrity. Experiment 2 indicated that a movie star's Facebook presence contributed to a more positive attitude toward the celebrity. A peer Facebook user's movie endorsement UGC resulted in greater advertising believability, more positive attitude toward, and more positive emotional reactions toward system-generated content (SGC) sponsored Facebook advertising than the movie star's self-promotion on his own Facebook page. In addition, movie involvement moderated the relationship between the Facebook profile source and advertising effectiveness. Highlights: The effects of Facebook profile sources on social networking advertising (SNA) were examined. Two experiments confirm warranting theory in Facebook-based celebrity brand endorsement. Other-endorsement more positively influences source credibility, PSI, and ad effectiveness than self-endorsement. Social identification with the endorser is a significant mediator. Involvement is a significant moderator.